Post-harvest tobacco pest control - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Post-harvest tobacco infestation control edited by L Ryan 1995 155pp ISBN 0 412 63130 X